Efficacy and compatibility of insecticides, fungicide and Rhizobium inoculant in combination for seed treatment in chickpea (Cicer arietinum) - CHEEMA, HARPREET KAUR; SHARMA, POONAM; SINGH, RAVINDER; TAGGAR, GAURAV KUMAR; KHANNA, VEENA; KOONER, B S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2005â€“08 to test the compatibility of the insecticides endosulfan and chlorpyrifos applied as seed treatment for the control of termites in chickpea (Cicer arietinum L.) with recommended fungicide Captan and Rhizobium inoculant. Insecticides endosulfan @ 15 ml/kg and chlorpyrifos @ 10 ml/kg seed had no adverse effect on germination, nodulation, yield-attributing characters and grain yield when applied alone or in combination with the recommended fungicide Captan and Rhizobium inoculant, thus, indicating the compatibility amongst all the 3 components, viz insecticide, fungicide and Rhizobium inoculant for seed treatment in chickpea. Â